Improved measures for evolutionary conservation that exploit taxonomy distances - Nawar Malhis (Nature Portfolio, 2019)
Information on protein sequence variability and conservation can be leveraged to identify functionally important regions. Here, the authors develop new conservation measures that exploit taxonomy distances and LIST, a tool for predicting deleteriousness of human variants.